Analisis saluran dan margin pemasaran cabai rawit (Capsicum frustescens L.) lokal Wamena di Kabupaten Jayawijaya - Rumbiak, Rein Edward Yohanes; Tuhuteru, Sumiyati (Universitas Musamus, Merauke, Papua, 2024)
It is recognized that there is potential for local cayenne pepper growing in the Central Highlands of Papua, namely in the Hubikiak District. Local cayenne peppers are distinguished by their taste and rather big form. As one of the hubs for generating regional cayenne pepper, Hubikiak District offers its own-harvested, locally grown cayenne pepper to merchants at a price that does not match the capital invested. The purpose of this study is to ascertain the quantity of the cayenne pepper marketing margin in Hubikiak District, Jayawijaya Regency, as well as to examine the structure of efficient marketing channels that contribute to the welfare of local Wamena cayenne pepper farmers. Because a feature of contemporary agriculture is that farming is done with an eye on making money. Hubikiak District was the site of this study, which ran from June to August of 2024. Marketing channel analysis and marketing margin analysis were the methods of data analysis that were employed. The results of the study show that the marketing channels for cayenne pepper in Hubikiak District, Jayawijaya Regency are divided into two, namely the first marketing channel (direct marketing channel) and the second marketing channel (indirect marketing channel) and the most effective in marketing local Wamena cayenne pepper is the first type of channel (direct marketing channel). Additionally, each marketing channel has an own margin value. There is a marketing margin in marketing channel I, which is the direct sale of agricultural products from farmers to customers, valued at IDR 20,000. In marketing channel II, the margin value is Rp. 30.000.